Anthelmithic activity of Methanolic extract of Phaseolus semierectus (L.) - Hasan, Hamid Ghaffoori; Babu, N. Dora (International Journal of Psychosocial Rehabilitation, 2020)
Phaseolus semierectus (L.). is the most significant genus in the family Fabaceae, which is commonly known as Purple been in India1. This study evaluates anthelmintic activity of methanol extract of Phaseolus semierectus (L.). on Indian adult earthworms, Pheretima posthuma (annelid).Aerial parts were extracted by using soxhlet apparatus. Phytochemical screening of crude extracts showed the presence of Alkaloids, Tannins, phenolics, flavanoids, terpenoids, steroids and proteins2. Various concentrations (25, 50, 100mg/ml) of crude extracts were tested for anthelminthic activity when involved the determination of the time of paralysis and time of death of worms. The activity was compared with standard piperazine citrate. The methanolic extract shows significant activity when compared to the standard piperazine citrate. The paralysis and death time is 56, 32, 18 and 77, 53, 34 minutes respectively at concentrations 25, 50 and 100mg/ml. whereas these are 31, 18, 10 and 63, 41, 22 minutes for piperazine citrate. In order to confirm the studies in vivo studies have to be conducted.